1990
DOI: 10.1021/bi00492a003
|View full text |Cite
|
Sign up to set email alerts
|

Small-angle scattering studies show distinct conformations of calmodulin in its complexes with two peptides based on the regulatory domain of the catalytic subunit of phosphorylase kinase

Abstract: Small-angle X-ray and neutron scattering have been used to study the solution structures of calmodulin complexed with synthetic peptides corresponding to residues 342-366 and 301-326, designated PhK5 and PhK13, respectively, in the regulatory domain of the catalytic subunit of skeletal muscle phosphorylase kinase. The scattering data show that binding of PhK5 to calmodulin induces a dramatic contraction of calmodulin, similar to that previously observed when calmodulin is complexed with the calmodulin-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 19 publications
5
54
0
Order By: Relevance
“…There is significant evidence for other entirely different types of CaM target complexes and therefore possibly different mechanisms of target activation. For example, low angle x-ray scattering data shows that whereas one of the two CaM-binding peptides from phosphorylase kinase (PhK5) induces a compact conformation in CaM, the other (PhK13) induces an extended conformation (46). Described above, we have shown that CaM adopts an extended conformation to activate edema factor.…”
Section: Fig 1 Sds-pagementioning
confidence: 55%
“…There is significant evidence for other entirely different types of CaM target complexes and therefore possibly different mechanisms of target activation. For example, low angle x-ray scattering data shows that whereas one of the two CaM-binding peptides from phosphorylase kinase (PhK5) induces a compact conformation in CaM, the other (PhK13) induces an extended conformation (46). Described above, we have shown that CaM adopts an extended conformation to activate edema factor.…”
Section: Fig 1 Sds-pagementioning
confidence: 55%
“…The flexibility was postulated in two senses: (i) to accommodate the functionality of linkers of various lengths in mutant CaMs and in homologs of CaM and (ii) to enfold target helices of various sequence and sense. Subsequently, small-angle x-ray scattering experiment measurements of CaM showed a shortening of CaM upon complexation with target helices (17)(18)(19)(20)(21). Des-Glu83, Glu84_ CaM and des-Ser81, Glu82, Glu83, Glu84-CaM are elongated in solution, as determined by experiments consistent with their having helical linkers two and four residues shorter than native CaM.…”
mentioning
confidence: 73%
“…This is somewhat unusual in that the extended conformation of calmodulin typically becomes more compact and globular upon Ca The two calmodulin-binding sites in the gamma-M subunit were first identified by peptide studies. Two synthetic peptides, denoted in the original literature as PhK5 (same amino acid sequence as residues 301-327 in gamma-M) and PhK13 (same amino acid sequence as residues 342-367 in gamma-M), have been used extensively to study potential gamma-delta interactions (21,38,43 The calmodulin-binding domain represented by PhK5 is predicted to fold into an amphipathic alpha helix, as, it is believed, do the calmodulin-binding domains in most other calmodulin target proteins (21,26). The PhK13 peptide, on the other hand, is predicted to fold into a beta-turn / beta-sheet, which could account for the more extended structure of calmodulin when bound to this peptide.…”
Section: The Delta Subunitmentioning
confidence: 99%
“…The PhK13 peptide, on the other hand, is predicted to fold into a beta-turn / beta-sheet, which could account for the more extended structure of calmodulin when bound to this peptide. When the PhK5 and PhK13 peptides bind simultaneously with calmodulin, calmodulin assumed an extended conformation [38,43]. it would therefore appear that the effects of the PhK13 peptide predominate over the effects of the PhK5 peptide and, by inference, that the delta subunit is more likely to be in an extended conformation when bound to the gamma subunit (21,36,38).…”
Section: The Delta Subunitmentioning
confidence: 99%